What Can Influence the Quality of International Collaborative Publications: A Case Study of Humanities and Social Sciences International Collaboration in China’s Double First-Class Project Universities - Zhe Cheng; Xingfu Lu; Xiong Xiong; Chuanyi Wang (Social Sciences, 2021)
International collaboration is one of the effective ways to enhance the impact of scientific research papers. In this research, international research collaboration papers published by world-class universities in the field of humanities and social sciences from 2015 to 2019 were selected as the research object, and the effective enhancement of the impact of international research collaboration papers was found to not be dependent on expanding the scale of international research collaboration, but rather on selecting researchers with different international backgrounds and from high-level institutions for collaboration. It was also discovered that, in the field of humanities and social sciences, despite a relatively low proportion of international research collaboration papers being led by Chinese scholars, the Chinese research is characterized by a higher impact compared with the research led by non-Chinese scholars. In light of this, a series of proactive measures should be taken by China’s world-class universities, such as actively participating in and initiating international collaboration, selecting high-level research collaborators, and attracting scholars from different countries to engage in research collaboration in the field of humanities and social sciences.